2016
DOI: 10.1021/acs.est.5b05947
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of the Immobile Zone in Non-Fickian Two-Phase Transport: A New Paradigm

Abstract: Using a visualization setup, we characterized the solute transport in a micromodel filled with two fluid phases using direct, real-time imaging. By processing the time series of images of solute transport (dispersion) in a two fluid-phase filled micromodel, we directly delineated the change of transport hydrodynamics as a result of fluid-phase occupancy. We found that, in the water saturation range of 0.6-0.8, the macroscopic dispersion coefficient reaches its maximum value and the coefficient was 1 order of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
99
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 51 publications
9
99
1
2
Order By: Relevance
“…In contrary to the column-scale experiments 17, 20, 21 , high-resolution real-time (optical and X-ray) imaging has lately allowed us to quantify directly the pore-scale mixing and transport in porous media 2224 even under two fluid phase conditions 25, 26 . From the hydro-dynamic point of view, the existence of two fluid phases in a porous medium will create some hydrodynamically stagnant zones in each fluid with very weak (close to zero) velocity fields, which will make the local transport regime to be diffusive.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrary to the column-scale experiments 17, 20, 21 , high-resolution real-time (optical and X-ray) imaging has lately allowed us to quantify directly the pore-scale mixing and transport in porous media 2224 even under two fluid phase conditions 25, 26 . From the hydro-dynamic point of view, the existence of two fluid phases in a porous medium will create some hydrodynamically stagnant zones in each fluid with very weak (close to zero) velocity fields, which will make the local transport regime to be diffusive.…”
Section: Introductionmentioning
confidence: 99%
“…25 Karadimitriou et al . 25 who directly quantified the stagnant zones and showed that the diffusive mass exchange rate between the mobile and the immobile region in the MIM model is time and flow-rate dependent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 In recent years, the additional oil extracted by tuning the composition of the injected water has revived the interest in a more detailed understanding of the nature of the interactions between the rock and the fluids residing in the pore. 318 …”
Section: Introductionmentioning
confidence: 99%